A prospective pilot study on plasma amyloid beta oligomers and postoperative delirium - Yang, YoungSoon; Jung, Ki Jin; Kwak, Yong Tae (Frontiers in Medicine, 2025)
IntroductionPostoperative delirium (POD) is common in older adults and has been linked to Alzheimer’s disease (AD). Plasma amyloid-β oligomers (AβOs) may clarify this relationship. We evaluated whether preoperative AβO burden is associated with POD severity.MethodsIn this single-center prospective pilot study, we enrolled 22 patients aged ≥65 years undergoing hip or knee arthroplasty under general anesthesia. Blood was drawn preoperatively and postoperatively to quantify oligomerized amyloid-β using the multimer detection system (MDS-Oaβ). POD was assessed with the Korean version of the Delirium Rating Scale-98 (K-DRS-98). Group comparisons and correlations examined associations between MDS-Oaβ and POD.ResultsEleven of 22 patients developed POD. Those with POD were older and had higher preoperative MDS-Oaβ than those without POD (0.81 vs 0.56 ng/mL). There was no significant perioperative change in MDS-Oaβ, suggesting surgery or anesthesia did not alter the plasma Aβ oligomerization tendency. Within the POD group, preoperative MDS-Oaβ correlated with both K-DRS-98 severity and total scores.DiscussionIn this pilot cohort, higher preoperative AβO burden was associated with the occurrence and severity of POD, while perioperative factors did not measurably affect AβO levels. These findings support a potential mechanistic link between AD-related pathology and POD. Given the small sample (N=22), estimates are imprecise and hypothesis-generating; validation in larger, multicenter studies is required before clinical application.